Effect of Tricalcium Silicate on Direct Pulp Capping: Experimental Study in Rats - Chicarelli, Lúcio P.G. (Eur J Dent, 2021)
Objectives Conduct a histological comparison of the pulp response to different materials, with a focus on the continuity and morphology of the mineralized barrier after direct pulp capping. Materials and Methods  One hundred and eight maxillary first molars of 54 Wistar rats were subject to direct pulp capping and divided into three groups according to the materials used: calcium hydroxide (CH), mineral trioxide aggregate (MTA), and Biodentine. All cavities were sealed, and the animals were euthanized at 7, 14, and 21 days. Descriptive histological evaluation of the inflammation and formation of the mineralized barrier was performed. Statistical Analysis  Statistical analyses were performed using the Kruskal–Wallis test, which was complemented by the Dunn test; differences with p < 0.05 were considered statistically significant. Results  The results showed that MTA and Biodentine elicited less intense inflammatory reactions than CH. With respect to the formation and quality of the dentin barrier formed, differences were observed at 21 days between the analyzed groups; the best results being obtained following treatment with MTA and Biodentine. Conclusion  MTA and Biodentine induced formation of a more continuous and uniform mineralized barrier with less intense pulp response than CH.